Insulin pump use and discontinuation in children and teens: a population‐based cohort study in Ontario, Canada1. Issue 1 (8th January 2016) - Shulman, Rayzel; Stukel, Therese A; Miller, Fiona A; Newman, Alice; Daneman, Denis; Guttmann, Astrid
Abstract : Objective: To describe insulin pump use by youth since introduction of universal funding in Ontario, Canada and to explore the relationship between pump use and pediatric diabetes center characteristics and the relationship between discontinuation and center and patient characteristics. Research Design and Methods: Observational, population‐based cohort study of youth with type 1 diabetes (<19 yr) who received pump funding from 2006 to 2013 (n = 3700). We linked 2012 survey data from 33 pediatric diabetes centers to health administrative databases. We tested the relationship between center‐level pump uptake and center characteristics (center type, physician model, and availability of 24‐h support) using an adjusted negative binomial model; we studied center‐ and patient‐level factors (socioeconomic status and baseline glycemic control) associated with discontinuation using a Cox proportional hazards model with generalized estimating equations. Results: Pump users were more likely to be in the highest income quintile than non‐pump users (29.6 vs. 19.1%, p < 0.0001). In 2012, mean percent pump use was 38.0% with variability across centers. There was no association between uptake and center characteristics. Discontinuation was low (0.42/100 person‐yr) and was associated with being followed at a small community center [hazard ratio (HR): 2.24 (1.05–4.76)] and being more deprived [HR: 2.36 (1.14–1.48)]. Older age was associated with a lower rate of discontinuation [HR: 0.31 (0.14–0.66)]. Conclusions: Rates of pump use have increased since 2006 and discontinuation is rare. Large variation in uptake across centers was not explained by the factors we examined but may reflect variation in patient populations or practice patterns, and should be further explored.